E-COMMERCE SEBAGAI PENDUKUNG PEMASARAN - Sugeng, Sugeng (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2017)
Electronic Commerce is the process of buying, selling or exchanging products, services and information via computer networks. e-commerce is part of the e-business, where the scope of ebusiness more broadly, not just commercial but also include business partners, customer service, job vacancies, products, information etc. In addition to networking technologies www, ecommerce technology also requires a database, e-mail or electronic mail , and the form of noncomputer technology as well as other delivery systems, and means of payment for e -Commerce. Given the electronic commerce (e-commerce) is then the customer can access and perform orders from various places or country. Given the current era of advanced technology is the customer who wants to access e-commerce does not have to be somewhere, it is because in the big cities in Indonesia have a lot of places that provide an internet access facility usingon the mobile phone, laptop / notebook or by Personal Digital Assistant using wifi technology. Thus the time is now very necessary and desirable companies to implement e-commerce services. The use of e-commerce in Indonesia is still very limited. Next time, Indonesia will be a best country for use of e-commerce system. From the background that there is then the author will discuss how e-commerce apply in their business interests especially on the marketing system. And this time, e-commerce needed to accreditation.